Anemia in Mexican women: a public health problem - Shamah-Levy Teresa; Villalpando Salvador; Rivera Juan A.; Mejía-Rodríguez Fabiola; Camacho-Cisneros Martha; Monterrubio Eric A (Instituto Nacional de Salud Pública, 2003)
OBJECTIVE: The purpose of this study is to quantify the prevalence and distribution of anemia among women of childbearing age (12 to 49 years) participating in the 1999 National Nutrition Survey (NNS-1999). MATERIAL AND METHODS: The survey had a probabilistic design and was representative at the national level, of urban and rural areas and four regions: North, South, Center, and Mexico City. Hemoglobin concentration was determined in capillary blood samples using a portable photometer (HemoCue), in 17 194 women, 697 of whom were pregnant. RESULTS: The overall prevalence of anemia was 27.8% in pregnant women and 20.8% in non-pregnant women. Higher prevalences were observed in rural as compared to urban areas, both in pregnant (28.0% vs 27.7%) and non-pregnant (22.6% vs 20.0%) women, but the differences were not statistically significant (p >0.05). Women in the South had the greatest prevalence (23.2%), followed by those in the North (20.9%), Center (20.6%), and Mexico City (16.4%). Non-pregnant indigenous women had a prevalence of 24.8%, while in non-indigenous women the prevalence was 20.4%. CONCLUSIONS: Anemia in women of childbearing age is a growing public health problem that justifies the implementation of interventions for its prevention and control.